Becoming an Anti-Racist Church : Journeying toward Wholeness - Barndt, Joseph R. (Book collections on Project MUSE., 2011)
Christians addressing racism in American society must begin with a frank assessment of how race figures in the churches themselves, leading activist Joseph Barndt argues. This practical and important volume extends the insights of Barndt's earlier, more general work to address the race situation in the churches themselves and to equip people there to be agents for change in and beyond their church communities.